Intertextual Patterns in Ibn Kathīr’s Muqaddimah: A Comparative Study with Ibn Taymiyyah’s Methodology - Wara, Jullul; Maram, Ahmad Nabilul; Ahmadi, Ahmadi (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
This study aimed to analyze the intertextual patterns found in the muqaddimah of Ibn Kathīr’s Tafsīr al-Qur’ān al-‘Aẓīm and its relation to Ibn Taymiyyah’s Muqaddimah fī Uṣūl al-Tafsīr to understand how classical exegesis practices evolved. A qualitative approach with an intertextual analysis framework focused on primary text comparison and thematic evaluation. The study identified vital patterns, including haplology, expansion, and transformation, illustrating how Ibn Kathīr integrated and adapted previous scholarly ideas to create his distinctive interpretative voice. Key results showed that these modifications were deliberate strategies emphasizing Qur'anic coherence and source authenticity. The findings underscore the innovative nature of classical Islamic scholarship and highlight the dialogic relationship between foremost scholars, demonstrating how intertextual strategies can shape religious literature. This analysis offers a foundation for future research on how scholarly interpretations were transmitted and adapted in other works. The paper includes detailed examples, references, and a comparative analysis of linguistic and thematic structures. Penelitian ini bertujuan untuk menganalisis keterkaitan antara pola-pola intertekstual yang ditemukan dalam muqaddimah Tafsīr al-Qur'ān al-'Aẓīm karya Ibn Kaṡīr dengan Muqaddimah fī Uṣūl al-Tafsīr karya Ibnu Taimiyah untuk memahami bagaimana praktik-praktik tafsir klasik berkembang. Penelitian ini menggunakan pendekatan kualitatif dengan kerangka analisis intertekstual yang berfokus pada perbandingan teks primer dan analisis tematik. Dalam penelitian ini, ditemukan pola-pola penting, termasuk haplologi, ekspansi, dan transformasi, yang mengilustrasikan bagaimana Ibnu Kathīr mengintegrasikan dan mengadaptasi gagasan-gagasan ilmiah sebelumnya untuk menciptakan suara tafsirnya yang khas. Hasil utama menunjukkan bahwa modifikasi ini merupakan strategi yang disengaja untuk menekankan koherensi Alquran dengan keaslian sumber. Temuan ini menggarisbawahi sifat inovatif dari kesarjanaan Islam klasik dan menyoroti hubungan dialogis antara para ulama terkemuka, menunjukkan bagaimana strategi intertekstual dapat membentuk literatur keagamaan. Analisis ini menawarkan sebuah landasan untuk penelitian di masa depan tentang bagaimana penafsiran ilmiah ditransmisikan dan diadaptasi dalam karya-karya lain. Penelitian ini mencakup contoh-contoh terperinci, referensi, dan analisis komparatif struktur linguistik dan tematik.